Klinisk termografi som diagnostiskt hjälpmedel vid rörelsestörning hos häst - Nordfeldt, Karl-Johan (SLU/Dept. of Large Animal Clinical Sciences, 2004)
Thermography is the assesment of the surface temperature of the horses body and it falls into the categori of physiological imaging. Thermography allows us to portray inflammation and changes in sympathetic tone in a graphical manner.